PLT and DBAR Investigations on MPDMAPP Doped PVA/PVP Blend. (May 2015) - Bhajantri, R F; Ravindrachary, V; Lobo, Blaise; Pujari, P K; Rathod, Sunil G; Naik, Jagadish; Hebbar, Vidyashree; H, Chandrappa
Abstract: Poly(vinylalcohol) (PVA)/Poly(vinylpyrrolidone) (PVP) blend films, doped with chalcone derivative (1-(4-methylphenyl)-3-(4-N, N, dimethylaminophenyl)-2-propen-1-one) (MPDMAPP) from 0.025 wt% up to 1 wt% were prepared using solution casting technique. The o-Ps lifetime τ3 is found to change little, from 1.61 ns at 0.025 wt% dopant concentration to 1.63 ns at 0.5 wt% dopant level, but drops to 1.4 ns at 1 wt% dopant concentration, indicating the onset of phase separation. The S-parameter of DBAR was found to be linearly related to the ortho-Positronium(o-Ps) intensity I 3 . The S-parameter drops significantly from 0.1 wt% up to 1 wt% doping concentration. This is supported by the XRD scans.